Lysosome-Targeted Biosensor for the Super-Resolution Imaging of Lysosome–Mitochondrion Interaction - Wang, Han; Fang, Guiqian; Chen, Huimin; Hu, Maomao; Cui, Yajuan; Wang, Boyang; Su, Yudong; Liu, Yu; Dong, Bo; Shao, Xintian (Frontiers in Pharmacology, 2022)
Background: The interaction between lysosomes and mitochondria includes not only mitophagy but also mitochondrion–lysosome contact (MLC) that enables the two organelles to exchange materials and information. In our study, we synthesised a biosensor with fluorescence characteristics that can image lysosomes for structured illumination microscopy and, in turn, examined morphological changes in mitochondria and the phenomenon of MLC under pathological conditions. Methods: After designing and synthesising the biosensor, dubbed CNN, we performed an assay with a Cell Counting Kit-8 to detect CNN’s toxicity in relation to H9C2 cardiomyocytes. We next analysed the co-localisation of CNN and the commercial lysosomal probe LTG in cells, qualitatively analysed the imaging characteristics of CNN in different cells (i.e. H9C2, HeLa and HepG2 cells) via structured illumination microscopy and observed how CNN entered cells at different temperatures and levels of endocytosis. Last, we treated the H9C2 cells with mannitol or glucose to observe the morphological changes of mitochondria and their positions relative to lysosomes. Results: After we endocytosed CNN, a lysosome-targeted biosensor with a wide, stable pH response range, into cells in an energy-dependent manner, cells treated with mannitol or glucose showed the same phenomena of MLC as untreated cells. SIM also revealed that conditions in high glucose induced stress in lysosomes and changed the morphology of mitochondria from elongated strips to round spheres. Conclusion: CNN is a new tool for tracking lysosomes in living cells, both physiologically and pathologically, and showcases new options for the design of similar biosensors.